Politics, Pandemics, and Trauma: Understanding and Addressing Latino Health Needs Through a Culturally-Informed Lens - Held, Mary Lehman; Villarreal-Otálora, Tatiana; McPherson, Jane; Jennings-McGarity, Porter (Frontiers in Public Health, 2022)
Latino communities in the United States (U.S.) have long endured trauma due to multiple intersecting social and political forces. New restrictive immigration policies since 2016 and the COVID-19 pandemic have each created novel stressors for Latino communities, while escalating the risk of mental health disorders and highlighting the communities’ vulnerabilities. The effects of these stressors have been particularly pronounced in southeastern states, such as Tennessee and Georgia, due to their state-level anti-immigrant legislation. Yet, we lack sufficient data to understand how these factors present among Latinos seeking services. To focus attention on the specific experiences of Latino communities living in the U.S. Southeast, the authors analyzed the perspectives of 44 service providers working with these communities in the region using qualitative data collected in an online survey administered during the COVID-19 pandemic and while President Trump’s exclusionary immigration policies were in force. Four themes were identified: (1) Latino communities’ strengths; (2) impact of the Trump administration on Latino communities; (3) impact of COVID-19’s on Latino communities; and (4) strategies to enhance service delivery in Latino communities. Results provide meaningful data to inform micro- and macro-level service delivery in two exclusionary policy states and beyond. Findings suggest future research should include other new immigrant destinations and explore perceptions of Latino community members.